2019–2020 Florida Citrus Production Guide: Irrigation Management of Citrus Trees - Davie M. Kadyampakeni; Kelly T. Morgan; Mongi Zekri; Rhuanito S. Ferrarezi; Arnold W. Schumann; Thomas A. Obreza (EDIS)
This 5-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. This chapter on irrigation management of citrus is largely taken from guidelines provided in SL253 Chapter 9 on trees prior to citrus greening: SL253/SS478: Nutrition of Florida Citrus Trees, 3rd Edition. A section has been added to cover recent findings on water use of trees affected by citrus greening and the impact this would have on the irrigation management considerations. Written by D. M. Kadyampakeni, K. T. Morgan, M. Zekri, R. S. Ferrarezi, A. W. Schumann, and T. A. Obreza, and published by the Agronomy Department, March 2019.